1983
DOI: 10.1002/j.1551-8833.1983.tb05195.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of holding time and temperature on conform numbers in drinking water

Abstract: Concern has often been expressed about the reliability of coliform counts from drinking water samples held in transit before analysis. Samples collected from a municipal distribution system were split, stored at ambient (22°C) and refrigerator (5'C) temperatures, and analyzed over time for total coliform and heterotrophic bacterial densities. Coliform populations declined significantly at both temperatures after 24 hours. The rate of decline was 2.5 orders of magnitude greater at 22" C than at 5'C. Average los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…McDaniels et al (1985) found 14 and 40 % mean reduction in recoveries from 6 to 30 h at 5°C of Enterobacter cloacea and Citrobacter freundii (total coliforms), respectively, seeded into drinking water samples. In an earlier study of naturally occurring total coliforms in drinking water, McDaniels and Bordner (1983) found a small amount of decline (as shown by a graph) between 6 and 30 h at 5°C, but did not present recovery numbers. Bacterial indicators in groundwater have been found to be more stable because of fewer predators, lower temperatures, and less available nutrients than in surface waters, thereby allowing for a longer holding time (McCarthy 1957;Bitton et al 1983).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…McDaniels et al (1985) found 14 and 40 % mean reduction in recoveries from 6 to 30 h at 5°C of Enterobacter cloacea and Citrobacter freundii (total coliforms), respectively, seeded into drinking water samples. In an earlier study of naturally occurring total coliforms in drinking water, McDaniels and Bordner (1983) found a small amount of decline (as shown by a graph) between 6 and 30 h at 5°C, but did not present recovery numbers. Bacterial indicators in groundwater have been found to be more stable because of fewer predators, lower temperatures, and less available nutrients than in surface waters, thereby allowing for a longer holding time (McCarthy 1957;Bitton et al 1983).…”
Section: Discussionmentioning
confidence: 86%
“…Other published holding times for fecal-indicator bacteria samples in surface water and groundwater range from 6 to 24 h depending on whether the samples are being analyzed for compliance or noncompliance purposes and whether they are potable or non-potable water (APHA 2005). Many of the published holding time studies are older studies done with drinking water samples (Standridge and Lesar 1977;McDaniels and Bordner 1983) or one more recent study done with surface water samples (Pope et al 2003); none were done using untreated groundwater. These studies found insignificant reductions in fecal-indicator bacteria concentrations in samples with a longer holding time and concluded that results generated within 24-30 h were comparable to those generated within 8 h of sample collection.…”
Section: Introductionmentioning
confidence: 97%
“…Regulatory agencies are increasingly requiring more emphasis on E. coli testing as part of programs aimed at curtailing waterborne disease. Holding time and temperature can have a significant impact on the density of microbiological indicators at the time of sample analysis (4,5,7). Recommendations for E. coli holding times range from 8 h (2,3,9) to 24 h (8), and holding temperatures below 10°C are generally considered acceptable (2,3,8,9).…”
mentioning
confidence: 99%
“…Studies of coliforms and aerobic pathogens in environmental and effluent water samples [24,30,34,37] have confirmed that refrigerated storage temporarily preserves the integrity of estimates of these communities over a short storage period. However, the anaerobic nature of the produced water samples and microbial populations considered in this study precludes direct comparison with these studies, and necessitates some important qualifications.…”
Section: Changes In Mpn Estimates Of Microbial Population Sizesmentioning
confidence: 91%
“…Refrigeration at 4°C slows substrate uptake and metabolism by many microorganisms without causing cell death [26], and is a common technique for mitigating distortion of environmental and wastewater samples during short-term storage [24,34,37]; however, the effectiveness of refrigeration for preserving oil fieldproduced water samples has not been documented. To the authors' knowledge, no published studies exist that examine the effects of storage on the anaerobic microbial communities relevant to oil field sampling in general or nitrate amendment studies in particular.…”
Section: Introductionmentioning
confidence: 99%